Size distribution measurement of microplastics using a temporally and spatially resolved inductively coupled plasma optical emission spectrometer (ICP-OES). Issue 8 (22nd July 2021) - Teramoto, Yoshiyuki; Kim, Hyun-Ha
Abstract : We studied microplastics in water using a temporally and spatially resolved ICP-OES with an inverted-type torch. Abstract : We studied polystyrene microspheres of 1.5 and 3 μm (substitute for microplastics) in water using an inductively coupled plasma optical emission spectrometer (ICP-OES). The samples were introduced as single monodisperse microdroplets at a high frequency. To increase the stability of sample introduction over that in the conventional method, microdroplets were dispensed in the direction of gravity by inverting the ICP torch. The atomization process of polystyrene microspheres in droplets was observed using a high-speed camera equipped with a double monochromator. The serial photographs of the emission process showed that the temporal characteristics of particle atomization were significantly dependent on the particle size. This suggests that the particle size can be estimated from the temporal characteristics of particle atomization depending on the particle size and emission intensity. Even at a high frequency (400 Hz) of sample introduction, the two peaks of 1.5 and 3 μm polystyrene microspheres could be distinguished in the particle size distribution measurements. Additionally, the estimated coefficient of variation (CV) of the 3 μm polystyrene microspheres was reasonable. Our study shows that the use of the temporally and spatially resolved ICP-OES with inverted-type torch is a powerful technique for estimating the size distribution of microplastics in water.